2022
DOI: 10.3389/fimmu.2022.880850
|View full text |Cite
|
Sign up to set email alerts
|

UVB-Induced Microvesicle Particle Release and Its Effects on the Cutaneous Microenvironment

Abstract: Ultraviolet B radiation (UVB) has profound effects on human skin that results in a broad spectrum of immunological local and systemic responses and is the major cause of skin carcinogenesis. One important area of study in photobiology is how UVB is translated into effector signals. As the skin is exposed to UVB light, subcellular microvesicle particles (MVP), a subtype of bioactive extracellular vesicles, are released causing a variety of local and systemic immunological effects. In this review, we highlight k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 166 publications
0
16
0
Order By: Relevance
“…The formation of PAF and PAFR agonists then allows for their binding with PAFR, a G protein‐coupled receptor, which increases calcium levels and activates mitogen‐activated protein kinases (MAPK). LPCAT2 is phosphorylated by MAPK, leading to a positive feedback loop that continually generates high levels of PAF 21 . Thus, inflammatory cells that express high levels of LPCAT2 will yield very high quantities of PAF.…”
Section: Platelet Activating Factor Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of PAF and PAFR agonists then allows for their binding with PAFR, a G protein‐coupled receptor, which increases calcium levels and activates mitogen‐activated protein kinases (MAPK). LPCAT2 is phosphorylated by MAPK, leading to a positive feedback loop that continually generates high levels of PAF 21 . Thus, inflammatory cells that express high levels of LPCAT2 will yield very high quantities of PAF.…”
Section: Platelet Activating Factor Pathwaymentioning
confidence: 99%
“…The use of pharmacologic inhibitors and knockout mice has indicated that the formation of MVP in response to many stimuli appears to be dependent on the translocation of the enzyme aSMase to the plasma membrane 17,33,38 . The initial step of MVP formation, the restructuring of the plasma membrane at the site of MVP production, has not yet been fully established, but the consequent components of the MVP gathering bioactive molecules and then budding and release of the MVP from the plasma membrane are dependent on aSMase 21,39,40 . The release of MVP which contain PAF and PAFR agonists proliferates PAFR activation throughout other cells, leading to PAF mediated systemic toxicity as a result of keratinocyte damage 30 .…”
Section: Mvps and Itbimentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular vesicles (EVs) are lipid bilayer structures secreted by living cells and are classified into either exosomes, microvesicles (MVs), or apoptotic bodies, based on the intracellular production mechanism and size ( Figure 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , …”
Section: Introductionmentioning
confidence: 99%
“…UV radiation is a major cause of photoaging, and can be divided into three bands [i.e., UVA (315-400 nm), UVB (280-315 nm) and UVC (100-280 nm)]. Of note, UVB is the predominant form that causes injuries to living organisms (Slominski et al, 2018a;Frommeyer et al, 2022). UV radiation not only induces skin pathology, but also exert systemic effects, including activation of hypothalamicpituitary-adrenal axis, opioidogenic effects, and immunosuppression.…”
Section: Introductionmentioning
confidence: 99%